KAJIAN SISTEM PANEN TERHADAP POTENSI CPO (CRUDE PALM OIL) DI AFDELING I KEBUN TANAH RAJA PT. BAKRIE SUMATERA PLANTATION, Tbk. - Tuty Ningsih; Hari Gunawan; Jhon F Parhorasan (Institut Teknologi Sawit Indonesia, 2021)
Harvest is one of determining factors to produce quality Fresh Fruit Bunches (FFB). Quality FFB is determining factors for Free Fatty Acids (FFA) and yield of the resulting oil. To produce good CPO potential, synergy is needed between the plantation part and the palm oil mill part. The research method used a descriptive method, namely to explain the harvest system and its relation to the quality of oil palm fruit. Observation data in the form of a harvest system consisting of Harvest Density Number (AKP) and random system used, Analysis of palm oil potential in the form FFB Analysis and CPO Yield. The Results showed that the harvesting system in division 1 Tanah Raja PT BSP used fixed sleigh and the potency test of palm oil showed that the CPO yield was 21.22% and FFA was 2,42%.